Six Types of Tea Reduce Acute Alcoholism in Mice by Enhancing Ethanol Metabolism, Suppressing Oxidative Stress and Inflammation - Lai, Xingfei; Wang, Xinrong; Wen, Shuai; Sun, Lingli; Chen, Ruohong; Zhang, Zhenbiao; Li, Qiuhua; Cao, Junxi; Lai, Zhaoxiang; Li, Zhigang; Sun, Shili; Liu, Xiaohui (Frontiers in Nutrition, 2022)
Acute alcoholic intoxication (AAI) is a pathological process of multiple system damage caused by a large amount of alcohol, especially in the liver. Although tea extracts alleviate AAI and alcohol-induced liver damage, the mechanisms underlying the protective actions of different types of Chinese tea are unclear. In this study, the AAI mice model was used to explore the functions and mechanisms of six types of tea extract (WEATs) in alleviating AAI. The losing righting reflexes of mice were evaluated to assess the effects of the WEATs on AAI. The levels of the ethanol metabolism enzymes (ADH, ALDH2, CYP2E1), the oxidative stress-related indicators (SOD, GSH, CAT, NRF-2, HO-1 and TG) and the inflammatory factors (TNF-α, iNOS, IL-6 and IL-10) were determined. Black tea and dark tea significantly shortened the sleep time (duration of the loss of righting reflex) and had a good sobering effect. Green tea and oolong tea had the dual effect of prolonging tolerance time (time of losing righting reflex) and shortening sleep time. While white tea had the most significant effect on prolonging tolerance time but with no obvious sobering effect. Black tea, dark tea and oolong tea significantly up-regulated ADH and ALDH2, and down-regulated CYP2E1. Green tea and white tea significantly increased the levels of GSH, CAT and NRF-2. Black tea, dark tea and oolong tea markedly increased the levels of HO-1, IL-10 and inhibited TG. Therefore, it is possible that black tea, dark tea and oolong tea reduced AAI by increasing ethanol metabolism, suppressing oxidative stress and inflammation. While green tea was mainly by regulating oxidative stress. White tea may prolong the tolerance time by increasing ethanol metabolism and reducing oxidative stress. Different types of tea have specific chemical compositions and can alleviate AAI. In conclusion, despite variations in the composition and mechanism of action, tea is a potent natural product to alleviate a hangover and protect the liver.